2015
DOI: 10.1002/2014jd022868
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative examination of lightning as a predictor of peak winds in tropical cyclones

Abstract: We use the World Wide Lightning Location Network to investigate lightning strike variations in 8 years of categories 4 and 5 tropical cyclones. A cross‐correlation analysis is performed between the lightning and maximum sustained wind variations, giving lag and lead times related to the peak linear correlation for each tropical cyclone. A previous study of 58 cyclones by Price et al. (2009) is reexamined using the International Best Track Archive for Climate Stewardship database for the maximum sustained wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…For example, increases in eyewall CG lightning flashes were also found in individual weakening TCs [Squires and Businger, 2008;Thomas et al, 2010]. Other studies found a strong positive correlation (r = 0.7-0.8) between CG lightning frequency and TC intensity for a significant number of major hurricanes [Price et al, 2009;Pan et al, 2014;Whittaker et al, 2015]. These studies analyzed CG lightning flashes within the entire TC, not subdividing by the INCO and OB regions, the latter dominating the TC total area.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…For example, increases in eyewall CG lightning flashes were also found in individual weakening TCs [Squires and Businger, 2008;Thomas et al, 2010]. Other studies found a strong positive correlation (r = 0.7-0.8) between CG lightning frequency and TC intensity for a significant number of major hurricanes [Price et al, 2009;Pan et al, 2014;Whittaker et al, 2015]. These studies analyzed CG lightning flashes within the entire TC, not subdividing by the INCO and OB regions, the latter dominating the TC total area.…”
Section: Discussionmentioning
confidence: 95%
“…Based on 5 years of TC samples in the northwestern Pacific basin, Zhang et al [] showed that RI TCs exhibit substantially higher INCO lightning density than rapidly weakening (RW) TCs, although INCO lightning density in RI and neutral TCs was similar. Other studies found a strong positive correlation ( r = 0.7–0.8) between lightning frequency and MSW in major hurricanes when the entire TC region is included [ Price et al , ; Pan et al , ; Whittaker et al , ]. These latter studies showed that TC peak intensity is preceded (~24 h) by increased cloud‐to‐ground (CG) lightning activity.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Especially for tropical hurricanes, several studies have shown that strong lightning activity occurred prior to the cyclones maximum intensity. For instance, Price et al () and Whittaker et al () showed in a climatological approach that the maximum of lightning impacts occurred approximately 1 day before hurricane winds attain their maximum speed. While numerous studies that investigate the relation between lightning and cyclones are devoted to tropical hurricanes, the relevant literature over the Mediterranean is limited.…”
Section: Introductionmentioning
confidence: 99%